ANALISIS YURIDIS GAGASAN PEMBERLAKUAN KEMBALI GARIS BESAR HALUAN NEGARA (GBHN) SEBAGAI PANDUAN PEMBANGUNAN NASIONAL PASCA AMENDEMEN. - Triandi Bimankalid; Dodi Haryono; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
After Amendment of the Constitution Republic of Indonesia in 1945, all of the component through their representatives in the Assembly agreed to eliminate the outline of the state policy of the Constitution of the Republic of Indonesia in 1945. The loss of the guidelines on policy in the constitution as and effects of the passing reformation. When the guidelines on policy as a national planning system, the idea to return the guidelines on policies to guide their national development make a lot of disappointment from many side of the constructor process who its outputs and outcomes are not as prescribed by the Constitution. Therefore, the purpose of this essay; First, to determine the urgency of the idea of resetting the Guidelines as a policy guide after changes in national development; Second, to determine the effects of Entry Aid Guidelines back on the institutional structure of the General Assembly.The type of research is used in the writing of this law is a normative legal research. Through the use of the method described in the literature, uses the data source, the primary data, secondary data and the data tertiary, data collection techniques in this study by means of a series of operations of the collection of data with the qualitative analysis that the descriptive data produces, by the study of the literature.The investigation there are two important things that can be inferred. First. Guidelines led to the re-enactment of urgency for their disappointment stakeholder development to concerned about the limited perspective elected president or head of the region, causing inequality in the development of the different regions. As stated guidelines Sovereignty Concrete embodiment seen from the formation process, it is called as reinforcement of checks and balances Principles directives, guidelines called proven ability to achieve national development a more successful, consistent and durable. Second, the implication is that if the desire to form the guidelines do not differ much with the guidelines, when the era of the Old Order and New Order, which is to return to the position of the Assembly as the highest institution and at the same time as the holder of sovereignty. During think giving a legal basis to control the legislative Act, the position of the Assembly as the highest setting is automatically revived and achievement system and Balances .. Sugestion author First come, the Institute of the General Assembly need not be included on the reintroduction of the guidelines in the plan amendment. Second, in addition SPPN reference development planning, planning should also be guided by the culture and customs of the local population, so the results permbangunan quickly accepted by the public.Keywords: GBHN-Amendement -MPR